Pemberdayaan Santri Melalui Kewirausahaan Peternakan Puyuh di Pondok Pesantren Al-Mustaqim Kecamatan Lawang Kabupaten Malang - Afandy, Randy Septian; Sabir; Warnaen, Andi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the role of Al-Mustaqim Islamic Boarding School in empowering students through quail farming entrepreneurship. The study used a descriptive qualitative method with research subjects including the head of the Islamic boarding school, managers of quail farming business units, and students involved in entrepreneurial activities. Data were collected through interviews, observations, and documentation, then analyzed using NVivo 12 software through the Word Cloud and Hierarchy Chart features. The results show that Al-Mustaqim Islamic Boarding School plays a role as a facilitator, educator, and mentor in the implementation of quail farming entrepreneurship. This program not only improves technical farming skills but also develops managerial abilities, responsibility, cooperation, discipline, and independence of students. In addition to providing a practice-based learning experience, these activities also support the strengthening of the Islamic boarding school economy through productive business management. The implications of this study indicate that the livestock entrepreneurship-based empowerment model in the Islamic boarding school environment can be an alternative vocational education strategy that integrates character building, entrepreneurial skills development, and economic independence so that it has the potential to be replicated in other Islamic boarding schools by adjusting to the conditions and resources available.